Industry 4.0, AI, and data science : research trends and challenges - Bali, Vikram (Boca Raton, FL : CRC Press, 2021)
"The aim of this book is to provide insight into Data Science and Artificial Learning Techniques based on Industry 4.0, conveys how Machine Learning & Data Science are becoming an essential part of industrial and academic research. Varying from healthcare to social networking and everywhere hybrid models for Data Science, Al, and Machine Learning are being used. The book describes different theoretical and practical aspects and highlights how new systems are being developed. Along with focusing on the research trends, challenges and future of AI in Data Science, the book explores the potential for integration of advanced AI algorithms, addresses the challenges of Data Science for Industry 4.0, covers different security issues, includes qualitative and quantitative research, and offers case studies with working models. This book also provides an overview of AI and Data Science algorithms for readers who do not have a strong mathematical background. Undergraduates, postgraduates, academicians, researchers, and industry professionals will benefit from this book and use it as a guide"--
OCLC-licensed vendor bibliographic record.
Keywords: Industry 4.0.; COMPUTERS / Database Management / Data Mining; BUSINESS & ECONOMICS / Operations Research; TECHNOLOGY / Manufacturing